Aldehyde-vegetable combination tanning for tuna fish skin. Issue 1 (1st July 2022) - Suparno, O; Hasibuan, D R S
Abstract: The tuna fish skin has a huge potential to be processed into leather through a tanning process. An environmentally benign tanning process, such as aldehyde-vegetable combination tanning in the manufacture of leather, is needed. This study aimed to determine the effect of the type of vegetable tannage and its concentration or dosage on the physical and organoleptic properties of the tuna skin leather and to determine the best combination of treatments. Tuna skin was tanned using 3% glutaraldehyde and vegetable tannages (mimosa, gambier, and quebracho) with dosages of 10%, 15%, and 20%. This study showed that the type of vegetable tannage has a significant effect on the thickness increase, shrinkage temperature, tear strength, and elongation at break of the resulting leathers. The dosage of vegetable tannage and the interaction of the two factors do not significantly affect the leathers' physical properties. The combination of tanning with 3% glutaraldehyde and 20% mimosa gives the best results in this study. The leather's physical properties are thickness increase of 20.8%, shrinkage temperature of 88.8 °C, tensile strength of 17.8 N/mm 2, elongation at break of 41.4%, and tear strength of 54.59 N/mm. Their organoleptic properties are flexibility (fell or handle) of 6-7 and colour of 7-8.